(untitled) (مجلة المنصور, 2022)
Iraq as one of the third world countries , Try to use his potential capacities to run the development machines . So that, the financial sector as considered as one of its institutions , which can play a major role with such trend according to his capabilities to allocate and specifies the resources with a good (efficient , flexible) financial and banking System .There fore, we need her to improve and develop the process of the financial institutes performance which can be used in the best way the available resource (Saving, Deposits , Credits … etc) and transferred to economic action from their investment with deferent sectors , with the assurance to find the solution to the problem that facing the financial procedures and to develop and expand their capabilities as well as increasing their experiences by using new techniques ( communication – networks, mis, …etc ) and problem- Solving that facing the banking System in order to be competitive with other banking institutes, and to be able to enter the Iraqi market as well as supporting the Iraqi economy by economic development sources